Influence of Rice Herbicides on Weed Growth and Nutrient Removal under Different Tillage in Rice–Yellow Sarson Cropping Sequence - Jaiswal, D. K.; Duary, B.; Madhukar, Bonthala; Jaiswal, Divya (International Journal of Bio-resource and Stress Management, 2022)
A field experiment was conducted during June–February, 2019–20 and 2020–21 to evaluate the impact of tillage and rice herbicides on weed growth, nutrient removal by weeds and the productivity of residual yellow sarson under rice–yellow sarson cropping. Two tillage system viz. zero tillage (ZT–ZT) and conventional tillage (CT–CT) in main plot and six herbicide combinations [oxadiargyl at 90 g ha-1 followed by (fb) bispyribac-sodium at 25 g ha-1, penoxsulam+cyhalofop-butyl at 180 g ha-1, oxadiargyl at 90 g ha-1 fb penoxsulam+cyhalofop-butyl at 180 g ha-1, fenoxaprop-p-ethyl+ethoxysulfuron at 90+15 g ha-1, oxadiargyl at 90 g ha-1 fb fenoxaprop-p-ethyl+ethoxysulfuron at 90+15 g ha-1 and pendimethalin at 1000 g ha-1 fb bispyribac-sodium at 25 g ha-1] along with unweeded and weed free check were assigned in sub plot in rice. Under ZT–ZT, the nutrient removal by weeds was found to be less, while, yellow sarson removed (uptake) greater amount of nutrients besides producing better growth attributes and yield as compared to those under CT–CT. Zero tillage (ZT–ZT) recorded 37.0 and 37.3% higher seed and stick yield of yellow sarson as compared to CT–CT. The herbicides applied in rice had no carryover effect on the growth and yield of the yellow sarson. However, oxadiargyl fb fenoxaprop-p-ethyl+ethoxysulfuron and oxadiargyl fb penoxsulam+cyhalofop-butyl were found to be better to control weeds in rice (92-95% Weed control efficiency) compared to other herbicide combinations (21–91%). Hence, the ZT–ZT system with oxadiargyl at 90 g ha-1 fb fenoxaprop-p-ethyl+ethoxysulfuron at 90+15 g ha-1 and oxadiargyl at 90 g ha-1 fb penoxsulam+cyhalofop-butyl at 180 g ha-1 appeared to be the best option for managing weeds, reducing nutrient loss and obtaining higher yield of yellow sarson under rice–yellow sarson sequence.